LIVING WITH RACCOONS: FROM CONFLICT TO COEXISTENCE (Biocenosis, 2013)
Unplanned urban growth is directly associated with an increase of conflicts between humans and wildlife. Probably, raccoons have been the most adaptable mammals to the conditions offered by urban centers. In the last five years, reports about these animals have increased in the Metropolitan Area of our country. Currently, raccoons represent an economic cost for all their damages caused to infrastructure, an investment of time repairing what was destroyed, and a potential risk to human and pets’ health. This paper aims to summarize the information generated in a forum held at the School of Biology at the Universidad de Costa Rica (UCR) in order to establish the necessary guidelines for a harmonious living with these animals. Clearly, it has become a problem that is beyond capacity for the institutions in charge of the management of wildlife health in our country. Immediate actions are required by academic and government authorities in search for a solution according to the Costa Rican idiosyncrasy.
Keywords: Urban ecology; Wildlife management; Animal and public health